Multimode CYTOP fiber interferometer: an experimental study - Chapalo, Ivan; Theodosiou, Antreas; Kalli, Kyriacos; Kotov, Oleg (My University, 2019)
A CYTOP multimode gradient index perfluorinated polymer fiber is experimentally investigated as a sensing element of a multimode fiber interferometer. Speckle patterns, formed at the output of CYTOP fiber, were measured and analyzed at two wavelengths for different excitation conditions, and for fiber lengths 20, 80, and 400 m. The influence of fiber length on selective mode excitation ability and the formation of speckle patterns were revealed. The interferometric response was investigated, when the CYTOP fiber was subjected to temperature and strain perturbations. The dependences of the interferometer's properties on wavelength and excitation conditions were analyzed by the measuring of interferometer's averaged transfer function.
Keywords: Fiber optic sensors; Intermodal interference; Multimode interferometer; Polymer fiber; Specklegram sensors